Effects of exporter and intermediary cultural similarity on relationship between quality and export performance of SMEs - Hamir Basah, Norliza (2018)
This study aims to examine the factors that influence the relationship between Malaysian exporting small and medium-sized enterprises (SMEs) and exporter intermediaries (EIs) which could potentially impact exporters’ performance. Building a relationship alone is not sufficient to achieve high export performance. The relationship quality (trust, commitment and cooperation) is critical as factors that should be managed by exporters to achieve sustainable relationships with their intermediaries in order to ensure an efficient internationalization process. Further, in order to develop such a relationship, cultural similarity between exporter and intermediary is suggested as an antecedent that can facilitate the development of a closer relationship. The findings of the influence of the critical factors’ (trust, commitment and cooperation) on the relationship between exporter and intermediary were mixed and inconclusive in the literature, particularly with regard to factors influence and how they influence exporters’ performance. Drawing from the previous literature, this study attempts to investigate the mechanism by which cultural similarity leads to exporters’ performance by focusing on five variables and one mediating factor (trust). Theoretical foundations were drawn from the Social Capital Theory (SCT), Internationalization Process Theory (IP) and Relational Exchange Theory (RET). A quantitative method was employed in this study. Primary data were collected from a sample of 203 SME manufacturing exporting firms in Malaysia for empirical verification. Structural Equation Modeling (SmartPLS) was used for data analysis. The structural model analysis revealed that all the direct and mediation hypotheses were significant. Twelve direct relationships were supported (cultural similarity-export performance; cultural similarity-effective communication; cultural similarity-knowledge sharing; effective communication-knowledge sharing; effective communication-trust; knowledge sharing-trust; trust-export performance; trust-commitment; trust-cooperation; commitment-cooperation; cooperation-export performance and cultural similarity-trust). Trust significantly serves as a mediator in the cultural similarity and export performance; effective communication and commitment, and knowledge sharing and cooperation relationships. The findings extended the application of the underpinning theories and their tenets in explaining the Malaysian SMEs’ export performance use foreign intermediaries.